2013
DOI: 10.2478/s11658-013-0109-9
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological significance of lamin A/C, lamin B1 and lamin B receptor mRNA expression in human breast cancer

Abstract: Lamin A/C (LMNA), lamin B1 (LMNB1) and lamin B receptor (LBR) have key roles in nuclear structural integrity and chromosomal stability. In this study, we have studied the relationships between the mRNA expressions of A-type lamins, LMNB1 and LBR and the clinicopathological parameters in human breast cancer. Samples of breast cancer tissues (n = 115) and associated non-cancerous tissue (ANCT; n = 30) were assessed using reverse transcription and quantitative PCR. Transcript levels were correlated with clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 69 publications
4
79
1
Order By: Relevance
“…These properties are not only relevant in various physiological processes, but are also attracting increasing interest in the study of cancer metastasis, as altered expression of lamins has been reported in a variety of human cancers (reviewed in 33 ). Breast cancer tumor cells, for example, often have reduced expression of lamins A/C, 43, 44 and loss of lamins A/C negatively correlates with disease-free survival. 43 The increased nuclear deformability associated with reduced lamin A/C levels may promote invasion of metastatic cancer cells into surrounding tissues and spreading through the vascular and lymphatic system, thereby constituting a substantial risk factor on top of gene-regulatory changes linked to altered lamin expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties are not only relevant in various physiological processes, but are also attracting increasing interest in the study of cancer metastasis, as altered expression of lamins has been reported in a variety of human cancers (reviewed in 33 ). Breast cancer tumor cells, for example, often have reduced expression of lamins A/C, 43, 44 and loss of lamins A/C negatively correlates with disease-free survival. 43 The increased nuclear deformability associated with reduced lamin A/C levels may promote invasion of metastatic cancer cells into surrounding tissues and spreading through the vascular and lymphatic system, thereby constituting a substantial risk factor on top of gene-regulatory changes linked to altered lamin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer tumor cells, for example, often have reduced expression of lamins A/C, 43, 44 and loss of lamins A/C negatively correlates with disease-free survival. 43 The increased nuclear deformability associated with reduced lamin A/C levels may promote invasion of metastatic cancer cells into surrounding tissues and spreading through the vascular and lymphatic system, thereby constituting a substantial risk factor on top of gene-regulatory changes linked to altered lamin expression. 33 Thus, an improved understanding of the multifaceted function of lamins has the potential to uncover novel therapeutic targets in cancer metastasis and diseases caused by mutations in nuclear envelope proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing reports indicate that altered lamin expression (rather than mutations) is found in many cancers, and often correlates with negative clinical outcomes [47,86,87]. For example, reduced expression of lamin A/C has been reported in breast [88,89] and cervical cancer [90], and is correlated with an increased recurrence of stage II and III colon cancer [91] and reduced disease free survival in breast cancer [89]. However, in other cases, increased A-type lamin expression is associated with disease progression, specifically in prostate, colon and ovarian cancers [92,93].…”
Section: Figurementioning
confidence: 99%
“…Other work has shown that the ability of myosin-II to deform the nucleus can be a decisive factor in limiting glioma migration into brain tissue (Beadle et al, 2008;Ivkovic et al, 2012), but cancer cells in general show no universal lamina phenotype (reviewed in Foster et al, 2010). Although low levels of A-type lamin have been correlated with increased reoccurrence of colon cancers (Belt et al, 2011), A-type lamin was also found to be upregulated in certain skin and ovarian cancers (Hudson et al, 2007;Tilli et al, 2003), and higher expression of these lamin proteins has been associated with better clinical outcomes in breast cancer (Wazir et al, 2013). Our own studies of tumor expansion in mouse flank have been suggestive of an association between moderately reduced levels of A-type lamin and increased invasiveness into the surrounding tissue, but a more complex relationship between the level of A-type lamin and clinical prognosis might be explained by the tenuous balance between the effect of the lamina on nuclear deformability compared with that on cell survival.…”
Section: Mechanotransduction To the Nucleus -Downstream Of Ecm And Laminmentioning
confidence: 99%